Strategi Pengelolaan Peningkatan dan Inovasi Terkait Kinerja Karyawan untuk Meningkatkan Loyalitas Karyawan pada UMKM Kosmetik Bunda Lubuk Begalung - Sari, Selvi Yoa; Fenia, Selvi Zola; Nadila, Nia (LPPM Universitas Dharma Andalas, 2025)
This community service activity was conducted at UMKM Kosmetik Bunda Lubuk Begalung, located in Padang City, with the aim of providing knowledge and practical skills to business owners and employees to improve performance and employee loyalty through innovative approaches. The program focused on training in human resource management strategies and the use of social media as a digital marketing tool. The methods involved interactive training, hands-on content creation practice, and participatory discussions. The results showed increased employee understanding of their strategic role within the business, improved skills in creating promotional content for social media, and more active engagement with consumers. Employee loyalty also improved as they felt more involved in the business development process. This activity demonstrates that combining performance management strategies with innovation and digital marketing can be an effective solution for MSMEs to retain employees and expand their market reach.